ANALISIS METODE ALTMAN Z-SCORE SEBAGAI ALAT PREDIKSI KEBANGKRUTAN DAN PENGARUHNYA TERHADAP HARGA SAHAM PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Andriawan, Nur Fadli; Salean, Dantje (Universitas 17 Agustus 1945 Surabaya, 2016)
The purpose of this study was to determine the predicted outcome of bankruptcy and also to test there is influence between independent variable is the value of the model financial ratios Altman Z-score as a predictor of bankruptcy with the dependent variable is the price of this stock.this research take secondary data through the financial statements of each company in Indonesia Stock Exchange website. The sample used in this study were six industrial company and pharmacy sector on Indonesia Stock Exchange. using normality test and simple linear regression. The results showed that from 2009 to 2013 the majority of the industrial company and pharmacy sector in the Indonesia Stock Exchange in the category of companies that good.for hypothesis testing results of this study showed a significant relationship between predicted bankruptcy by using the value of financial ratios Altman Z-score the stock price at the industial company and pharmacy sector in the Indonesia Stock Exchange with the level of determination coefficient of 52%.Keywords: Altman Z-score, prediction of bankruptcy, the stock price